History of Tuva in the Soviet Period: A Problem-based, Objective and Tactful Approach - Oplakaskaia, Renata V. (The New Research of Tuva, 2017)
This is a review of: Istoriia Tuvy [The History Of Tuva] (2016) : in 3 vols. / ed. by N. M. Mollerov. Novosibirsk, Nauka. 455 p. (In Russ.). This final volume in the series takes on from the two previous volumes of the new edition of the “History of Tuva” (2001 and 2007). It has been prepared by a team of scholars at the Tuvan Institute for the Humanities and Applied Social and Economic Studies, in collaboration with their colleagues from elsewhere. The continuity of the history-writing tradition can be found in the formation-based civilizational approach, which has been chosen as the main theoretical and methodological basis for the study. This has predetermined the periodization and the overall structure of the book. It starts with examining the events in Tuva in 1944-1961, when Tuva joined the Soviet Union as an autonomous oblast within the RSFSR, and goes on to the events of 1961-1991, when Tuva’s status was elevated to that of autonomous republic. The volume ends at the point of USSR’s collapse. The team of authors came up with a complete and full description of how the region developed in the political, legal, social, economic and cultural aspects, with due attention to Tuva’s ethnic specifics. The rich factual background is well-structured, and the authors’ conclusions find ample proof in tables and diagrams. The authors treat sensitive issues, such as the Great Purges or optimization of political and economic processes within the state. The contradictions that a society inevitably faces on the path of rapid modernization, are shown here in both objective and a very tactful way.